Del taller artesanal a la Comparsa Selva Africana: Diálogos con la familia Llanos de Galapa-Atlántico (2021)
This document exalts the artistic and plastic contributions of the troupe called “Selva Africana” from Galapa Atlántico, whose origin goes back to an artisanal exercise that over the years have been developing esthetics and creative dynamics, making the community become an important part of the celebrations of the Barranquilla Carnival, and making visible the Galapa municipality. Form other side, this presents the geographic, social, and cultural context of Galapa with the purpose of safeguard and reproduce their artistic and creative practices through processes of teaching-learning